2005
DOI: 10.1128/aem.71.7.3725-3733.2005
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Population Dynamics of Anaerobic Methane-Oxidizing Archaea and Sulfate-Reducing Bacteria in a Continuous-Flow Bioreactor

Abstract: The consumption of methane in anoxic marine sediments is a biogeochemical phenomenon mediated by two archaeal groups (ANME-1 and ANME-2) that exist syntrophically with sulfate-reducing bacteria. These anaerobic methanotrophs have yet to be recovered in pure culture, and key aspects of their ecology and physiology remain poorly understood. To characterize the growth and physiology of these anaerobic methanotrophs and the syntrophic sulfate-reducing bacteria, we incubated marine sediments using an anoxic, contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
129
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(141 citation statements)
references
References 40 publications
9
129
0
3
Order By: Relevance
“…Sequences of the Thermoplasmatales were also found (13.6%). Their functioning is also unclear, but they have previously been found to co-occur with ANMEs (Hinrichs et al, 1999;Orphan et al, 2001;Inagaki et al, 2004;Girguis et al, 2005;Knittel et al, 2005;Wegener et al, 2008). Interestingly, no Crenarchaeota were found although they are common members of seep communities (Knittel et al, 2005;Lösekann et al, 2007).…”
Section: Identity Of Aom Communitiesmentioning
confidence: 88%
“…Sequences of the Thermoplasmatales were also found (13.6%). Their functioning is also unclear, but they have previously been found to co-occur with ANMEs (Hinrichs et al, 1999;Orphan et al, 2001;Inagaki et al, 2004;Girguis et al, 2005;Knittel et al, 2005;Wegener et al, 2008). Interestingly, no Crenarchaeota were found although they are common members of seep communities (Knittel et al, 2005;Lösekann et al, 2007).…”
Section: Identity Of Aom Communitiesmentioning
confidence: 88%
“…For example, several types of continuous-flow bioreactor systems have been developed and applied for the enrichment and cultivation of archaeal anaerobic methanotrophs (Girguis et al, 2003(Girguis et al, , 2005Meulepas et al, 2009;Zhang et al, 2010). Girguis et al, (2003Girguis et al, ( , 2005) developed a continuous-flow incubation system to mimic the in situ conditions of methane seep marine sediments and reported an increase in the archaeal anaerobic methanotroph population associated with the anaerobic oxidation of methane in the incubation system. Meulepas et al, (2009) also demonstrated that the oxidation of methane rate in a continuous submergedmembrane bioreactor increased exponentially from 0.4 to 286 mmol g dry weight…”
Section: Discussionmentioning
confidence: 99%
“…There are clearly a few lineages where little is known, and these should be targets for future work. Among these are anaerobic methanotrophs, which have been kept alive in their original sediment for study along with their sulfate-reducing bacterial counterparts (189,402) but never isolated in pure culture. Similarly, microorganisms from deep subsurface oceanic crust have eluded cultivation.…”
Section: Cultivated Prokaryotes From the Dark Oceanmentioning
confidence: 99%